Experiences of nurse educators in Malaysia regarding problem based learning / Umadevi Alasingam - Umadevi , Alasingam (2021)

(untitled)
In 2010, declining standards of nursing care in Malaysia triggered immense concern. This erosion was traced to inadequate teacher-centric nurse instruction in nursing schools. The Malaysian government proposed that Problem-based learning, a student-led instruction method, be utilized henceforth. This study aims to investigate the experiences of nurse-educators regarding Problem-based learning presuming that successful implementation of Problem-based learning method hinged heavily on the role, capabilities and attitude of nurse-educators regarding this divergent learning method. A study was conducted among five nurse-educators with long experiences in using this method. They were interviewed using open-ended questions. Interview data obtained was analyzed using N-Vivo-12 analytical software. The findings indicated that the nurse-educators had limited knowledge of Problem-based learning techniques, lacked adequate training in facilitating and exhibited insufficient conviction in utilizing Problem-based learning in its entirety in their teaching functions. The findings revealed that these nurse-educators complemented Problem Based learning with lectures and notes. A related finding was the poor support extended by management to these nurse-educators and the lack of monitoring of implementation of Problem-based learning. The significance of this study lies in the expose on the educators’ experiences adding to the limited research and information hitherto available regarding Problem-based learning- educator perceptions. The findings point towards educator preference for mixed-mode instruction rather than sole reliance on Problem-based learning.